Si San Ignacio, p'wera bola - Go, Johnny; Alvarez, Francis (Jesuit Communications, 2000)
A documentary on the life of St. Ignatius of Loyola, as presented by four Jesuit scholastics, and how their knowledge of him has changed their lives.